ANALISIS PENGARUH MADDEN JULIAN OSCILLATION TERHADAP PROPAGASI DAN DISTRIBUSI TEMPORAL HUJAN BERDASARKAN PENGAMATAN CITRA SATELIT DI WILAYAH BENGKULU TAHUN 2018 - Rizky Umul Nisa Fadillah; Yosafat Donni Haryanto; Nelly Florida Riama (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Madden Julian Oscillation (MJO) is a phase that produces variations in several parameters of the atmosphere and oceans which is indicated by the increase of rainfall in the area it passes through. Bengkulu region is the closest area to the initial area of the formation of the MJO. This study aims to determine the value of the connectivity as well as the propagation and temporal distribution of rain in the Bengkulu region during the active MJO period in phase 3 to phase 5 based on satellite imagery observations as well as the increase and decrease in rainfall in the Bengkulu region. Based on the descriptive analysis, it shows a weak convective state at 00 UTC and a strong convective at 12 UTC accompanied by rainfall propagation which is seen in phase 3 moving from west to east with changes in rainfall intensity at each active MJO phase from the Fatmawati Class III Meteorological Station Bengkulu, Bengkulu Class I Climatology Station and Kepahiang Bengkulu Class III Geophysical Station. From the observed phase period, the rainfall propagation pattern was seen in phase 3 and was followed by an increase in rainfall intensity, while in phases 4 and 5 there was a decrease in rainfall intensity that occurred in the Bengkulu region. MJO also has an effect on the increase in rainfall in the land area and waters of Bengkulu in phase 3 and phase 4. In phase 5 the decrease in rainfall occurs in the mainland area of ​​Bengkulu while the increase in rainfall occurs in Bengkulu waters